THE PROTECTION OF CHILD CUSTODY POST-DIVORCE BASED ON THE THEORY OF JUSTICE - Meilan Lestari; Syafrinaldi; Abd Thalib (International Conference On Law And Social Sciences, 2024)
Every human being needs justice for himself and his life. Justice is equal proportion, not one-sided, balanced and taking sides with the right, adhering to the truth, supposedly, not being arbitrary towards others and fulfilling the rights and duties towards other human beings including children. Children are a mandate entrusted by Allah to both parents who should be nurtured, educated, treated, and cared for with love, because children are the future successors of the family and a great responsibility for both parents. Child Custody is also known as Hadhanah, Hadhanah is the nurturing of a young child after a divorce. Divorce is the breakup of the physical and mental relationship between husband and wife, which causes the children to be separated from their father or mother, however, it should not decrease the attention and love for the children and meet the rights of the children they need in terms of educating, nursing, monitoring and providing livelihoods for children, because children are victims of their parents' divorce. Children are the sole responsibility of both parents, and the fulfilment of their right to education and nursing is something that needs special attention. The responsibility to care for and educate children lies with both parents, even if a court decision decides that the child's rights should be given to one of the parents.